Estudio de impacto ambiental de la granja avícola "El Camperito" ubicada en el sector-Cascarillal en el Cantón Piñas, provincia de El Oro -Ecuador - Aguilar Marín, Tatiana Yamile (2019)
The present investigation consisted of carrying out an environmental impact study of the “El Camperito” poultry farm located in the Cascarillal sector, Piñas province of El Oro-Ecuador, which aimed to carry out an environmental impact study, through the survey of the baseline with the characterization of the abiotic component such as climate, water quality, noise and soil and identification of the biotic component through the survey of flora, fauna and the characterization of the socioeconomic component through surveys of workers and residents close to the farm. The classification of the most significant environmental impacts was carried out through the application of the importance matrix by executing a qualitative and quantitative assessment of the impacts in 12 ranking criteria. An environmental management plan was designed for prevention, mitigation, environmental training, control, waste management, rehabilitation of affected areas and the remediation of impacts generated at the “El Camperito” poultry farm. The investigation revealed that the soil and water component are not affected, while the air component is affected by the bad odors generated by the excreta, where noise levels exceed the maximum permissible limits [64.2 dB (A)] established by the Unified Text of Secondary Legislation of the Ministry of Environment (2015), the background noise level of 10 dB (A) should not be exceeded. The environmental impacts detected in the operation phase were the generation of odors (-60) where the effect is critical and positive impact being the generation of employment (+59). In the closing phase, the component with the greatest impact was air due to gas contamination (-39), its effect was moderate. Keywords: environmental impact study, importance matrix, environmental impact, environmental management plan, poultry farming.